Development of an E-Magazine Based on Ethnoscience of Semarang's Traditional Food in the Topic of Temperature and Heat to Train Students' Scientific Literacy Skills - Sudarmin; Febriyanto, Hendra; Naufal, Muhammad; Eralita, Norma; Budoyo, Joto; Anisah, Siti; Safitriani, Indah (Indonesian Journal Publisher, 2025)
This study aims to analyze the characteristics, feasibility, and effectiveness of an e-magazine based on ethnoscience of Semarang's traditional food on the subject of temperature and heat to train students' scientific literacy skills. The Research and Development (R&D) method, utilizing the ADDIE model, was employed. The study involved VII D class students at SMP Negeri 5 Semarang, with data collected through feasibility validation, pretest, posttest, and student responses. The results showed that the characteristics of the e-magazine produced include an attractive and colorful visual design, compatibility with various devices, efficiency, practicality, and flexibility, interactive features, an ethnoscience approach, science literacy aspects, and encouragement of independent learning. The findings indicate the e-magazine is highly feasible for use, scoring 96.11% for media aspects, 96.21% for content aspects, and 91% for student readability. Its effectiveness in improving science literacy was statistically significant (Wilcoxon test 0.00 < 0.05). An N-Gain score of 0.73 indicates a high improvement in science literacy, with an overall effectiveness level of 73% (moderately effective category). In conclusion, the ethnoscience-based e-magazine on Semarang's traditional food supports innovative learning, is highly suitable as a learning medium, and is sufficiently effective in developing students' science literacy skills.